Desiccation tolerance in seeds of Annona emarginata (Schldtl.) H. Rainer and action of plant growth regulators on germination - Corsato, Jaqueline Malagutti [UNESP]; Ferreira, Gisela [UNESP]; Barbedo, Claudio Jose (FapUNIFESP (SciELO), 2012)
Annona emarginata (Schldtl.) H. Rainer (araticum-de-terra-fria) is used as a rootstock for several species of Annonaceae. It is suggested that these seeds should be sown immediately after extraction and, therefore, they could be intolerant to desiccation. There are several mechanisms involved with desiccation tolerance. Soluble sugars, for example, can accumulate and act as osmoprotectants for the membrane system during desiccation. The aim of this study is to assess desiccation tolerance in A. emarginata seeds. In addition, we examined the soluble sugars involved in desiccation tolerance. Finally, we determined the effect of gibberellic acid (GA4+7) and N-(phenylmethyl)-aminopurine in promoting the germination of seeds with different water contents. The experiment consisted of a randomized 4×5 factorial design (desiccation levels × concentration of growth regulators). After drying, seeds containing 31 (control), 19, 12 and 5% water were incubated in different concentrations of GA4+7 N-(phenylmethyl)-aminopurine (0, 250, 500, 750 and 1000 mg L-1) for 60 hours. The experiment was conducted in a germination chamber with alternating temperature and photoperiod of 20oC for 18 hours of darkness and 30oC for 6 hours of light. We analyzed electrical conductivity, germination rate, mean germination time, germination speed, frequency and uniformity of germination, percentage of dormant seeds and soluble sugar profile in intact seeds through high-performance liquid chromatography (HPLC). The data were subjected to analysis of variance, and the means were compared using Tukey's test at a threshold of p<0.05. The results showed that seeds of A. emarginata appears to be desiccation tolerant and, also, that sucrose increases when seed water content is reduced to values as low as 12%, exogenous GA4+7+N-(phenylmethyl)-aminopurine improves its germinability.
Keywords: Araticum-de-terra-fria; Cytokinins; Desiccation; Gibberellins; Soluble sugars